Association of Emotional Intelligence and Professional Socialization in Operating Room Students - R Niknejad; M Akbari; J Moghaddasi; A Ghadami (Iran University of Medical Sciences, 2018)
Background & Aims: Socialization is a constant process throughout human life. The enhancers of socialization must be identified in order to promote this process. The present study aimed to investigate the correlation between the emotional intelligence and professional socialization of the operating room students at Isfahan University of Medical Sciences, Iran. Materials & Methods: This cross-sectional, correlational study was conducted on 93 operating room students at Isfahan University of Medical Sciences after determining the sample size. Data were collected using a demographic questionnaire, Shirring and Siberia self-report questionnaire of emotional intelligence, and professional socialization questionnaire by Toit. Data analysis was performed in SPSS version 16 using descriptive and inferential statistics. Results: The results of Pearson's correlation-coefficient indicated direct correlations between the professional socialization of students and the total score of emotional intelligence (P=0.04), social component (P<0.001), empathy (P=0.04), and self-awareness (P=0.045). However, no significant associations were observed between emotional intelligence and the other components (P>0.05). Conclusion: According to the results, it seems that the professional socialization of operating room students is remarkably influenced by emotional intelligence and the level of learning in the academic environment. Given the importance of intelligence and socialization in the clinical environment and comprehensive patient care, clinical students must be adequately trained on emotional intelligence skills.